2000
DOI: 10.1001/archinte.160.20.3144
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Assessment of Psychological Well-being in a Randomized Placebo-Controlled Trial of Cholesterol Reduction With Pravastatin

Abstract: Background: There is controversial evidence that a low serum cholesterol level is associated with an increased risk of depression, suicide, and violence. The aim of this study was to identify or exclude any small or infrequent adverse effect of long-term reduction of serum cholesterol with pravastatin sodium on psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 52 publications
4
57
2
Order By: Relevance
“…In addition, we observed no significant difference as a function of LLA use, suggesting that absolute low levels rather than reduction from high lipid concentrations might be associated with depression. This is in agreement with randomized controlled trials in which no modification in depressive symptomatology has been reported in patients with, or at risk of, coronary disease receiving LLA (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we observed no significant difference as a function of LLA use, suggesting that absolute low levels rather than reduction from high lipid concentrations might be associated with depression. This is in agreement with randomized controlled trials in which no modification in depressive symptomatology has been reported in patients with, or at risk of, coronary disease receiving LLA (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…16,17,34 In the current analysis of women with chest pain, we found no difference in depressive symptoms between those receiving and not receiving a cholesterol-lowering treatment. Reports of adverse mood effects of cholesterol reduction generally derive from relatively small studies.…”
Section: Discussioncontrasting
confidence: 56%
“…10,11 Based on a prior report based on WISE study participants and evidence from other investigators, neither low nor lowered cholesterol is consistently associated with hostility or anger. 17,40,41 On the other hand, it is not known if cholesterol-lowering treatments per se affect aggressive behavior or cause the feeling of aggression toward others. In experiments using nonhuman primates, animals assigned to cholesterol-lowering diets acted more aggressively and exhibited less affiliative behavior than those on a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] No disutility from taking a pill everyday was assumed in the model. 50,51 In the rare case of nonfatal rhabdomyolysis or myopathy, disutility of 0.530 was applied for 1 year. 52 Utilities and life expectancies were multiplied to calculate qualityadjusted life years (QALYs).…”
Section: Costsmentioning
confidence: 99%